Biological associations of color variation in the Indo-Pacific swimming crab Charybdis hellerii - Watanabe, Timoteo T.; Zara, Fernando J. (UNESP); Hattori, Gustavo Y.; Turra, Alexander; Sant'anna, Bruno S. (Academia Brasileira de Ciências, 2015)
A marine biological invasion is a natural process accelerated by human activities, and the crab Charybdis hellerii is an example of a globally widespread invasive species. This study evaluated color variation in C. hellerii and its relationship to the sex, size and sexual maturity of these crabs, and compared the efficiency of a freeware digital image-editing program with a commercially available program. The color of the individuals was analyzed using standardized digital images. The color pattern varied significantly with size; smaller and immature individuals were darker than larger and mature ones. The female abdomen changed in morphology and color with sexual maturity, becoming wider and orange-colored. There was no statistical difference in the color values between males and females and immature males did not show morphological or color differences in their abdomen. This study highlights the possible relationships of the color and physiological state of the reproductive system, which could help in future studies of behavior, avoiding the need to dissect and/or remove individuals from nature for assessment of sexual maturity. The freeware program showed the same efficiency in digital image analysis as a widely known commercial program.

Invasões biológicas marinhas são processos naturais acelerados pelas atividades humanas e o siri Charybdis hellerii é um exemplo de espécies invasoras distribuídas pelo mundo. Este estudo avaliou a variação de cor em C. hellerii e sua relação com o sexo, tamanho e maturidade sexual desses indivíduos, e comparou a eficiência de um programa de edição de imagem de licença livre com um programa disponível comercialmente. A cor dos indivíduos foi analisada usando imagem digital padronizada. O padrão de cor variou significantemente com o tamanho; indivíduos pequenos e imaturos são mais escuros que indivíduos maiores e maduros. Os abdomens das fêmeas mudaram morfologicamente e na cor de acordo com a maturidade sexual, tornando-se mais largos e de cor alaranjada. Não houve diferença estatística nos valores de cor entre machos e fêmeas, e machos imaturos não mostraram diferenças morfológicas e de cor em seus abdomens. Este estudo ressalta as possíveis relações da cor e estado fisiológico do sistema reprodutivo o que pode ajudar futuramente em estudos comportamentais, evitando a necessidade de dissecar e/ou remover indivíduos da natureza para avaliar a maturidade sexual. O programa livre obteve a mesma eficiência na análise de imagem digital em relação ao programa comercial amplamente conhecido.
Keywords: Brachyura; Coloration variation; Digital image; Portunidae; Brachyura; Variação de cor; Imagem digital; Portunidae